BERAT POTONG, BERAT KARKAS DAN PERSENTASE KARKAS TERNAK SAPI POTONG LOKAL YANG DIPOTONG DI RUMAH POTONG HEWAN MANADO - Marino, Fernando Andris; Lomboan, A.; Pudjihastuti, E.; Sondakh, E.H.B. (ZOOTEC, 2020)
SLAUGHTER WEIGHT CARCASS WEIGHT AND THE PERCENTAGE OF CARCASSES OF NORTH SULAWESI LOCAL BEEF CATTLE CUT IN SLAUGHTER.The study aims to determine the slaughter weight, carcass weight  and  the percentage of carcasses of North Sulawesi local beef cattle cut in RPH Manado. The material used in this study were 40 local North Sulawesi beef cattle in RPH, Manado. The equipment used in this study is the meter and the hanging scales. This study uses the method of observation, direct interviews and measurements carried out randomly and weighing to determine the cut weight, carcass weight and carcass percentage. The results showed that the average value of 271,475 kg ± 34,129 kg weight, carcass weight 136,025 kg ± 16,477 and the percentage of North Sulawesi local beef cattle carcass 50,168% ± 1,694. Based on the results of the study it was concluded that the cattle of North Sulawesi local beef cattle slaughtered in RPH Manado still relatively low in term of average weight of slaughter and carcass weight. Keywords: Beef Cattle, Weight, Slaughterhouse